Posterior Reversible Encephalopathy Syndrome Associated with Late onset Eclampsia: A Case Report - Shah, Sonu; Joshi, Bishal Raj; Dhakal, Anil; Karki, Umesh; Surkheti, Bikash; Paneru, Monica; Shrestha, Robinson; Khatiwada, Sameen; Kafle, Dilli Ram (Journal of Nobel Medical College, 2023)
We describe a case of 25 year old women who had full term pregnancy, presented with symptoms of headache, loss of vision and seizure episodes after 7th postpartum day. There were no findings of pre-eclampsia in antenatal stage. The diagnosis of posterior reversible encephalopathy syndrome was made after magnetic resonance imaging. Imaging findings include vasogenic edema of bilateral occipital lobe and parietal lobe. Hypertension and endothelial injury seems to be involved in pathophysiology of the syndrome. After appropriate management, the syndrome resolved. Early diagnosis and proper treatment plays a key role in management of posterior reversible encephalopathy syndrome.